Dystrophic epidermolysis bullosa pruriginosa: a new case series of a rare phenotype unveils skewed Th2 immunity. (15th October 2021) - Darbord, D.; Hickman, G.; Pironon, N.; Barbieux, C.; Bonnet‐des‐Claustres, M.; Titeux, M.; Miskinyte, S.; Cordoliani, F.; Vignon‐Pennamen, M.D.; Amode, R.; Hovnanian, A.; Bourrat, E.
Abstract: Background: Dystrophic epidermolysis bullosa pruriginosa (DEB‐Pr) is a rare subtype of hereditary epidermolysis bullosa, with a poorly understood pathogenesis and no satisfactory treatment. Objectives: To assess the clinical and biological features, genetic basis and therapeutic management, to better characterize this rare genodermatosis. Methods: We have conducted a retrospective study, reviewing the clinical presentation, genetic diagnosis, immunohistopathological findings and biological characteristics and management of patients with dystrophic epidermolysis bullosa pruriginosa. This study was conducted in the Department of Dermatology at Saint‐Louis Hospital and the Department of Genetics at Necker Hospital (Paris, France). All patients with a diagnosis of DEB‐Pr seen between 2010 and 2020 were included. Results: Seven patients were included, the average age of 50.1 years [range 36–76]. Pruriginous‐lichenified papules, plaques or nodules appeared at 27.6 years on average [range 7–66] on pretibial areas and forearms, associated with milia and toenails dystrophy. All patients received multiple treatments, but none could sustainably reduce pruritus. Immunohistopathological analysis of lesion skin revealed subepidermal blister with fibrosis, milia and mast cell infiltration. Serum TNFα, IL1β and IL6 levels were elevated in 2/6 patients. Total serum IgE levels were increased in 7/7 patients, with no history of atopy. Immunophenotyping of circulating T‐cells revealed an increased Th2 subset in 4/4 patients, with reduced Th1 and Th17 subpopulations. Genetic analysis of COL7A1 identified 7 distinct causative mutations, six of which were new. Intra‐familial clinical variability was documented in 5/7 patients and was associated with the co‐inheritance of a recessive COL7A1 mutation or an FLG2 mutation in 2 families. Conclusion: Our study confirms the stereotyped presentation of DEB‐Pr with large intra‐familial variability in disease expression. Mast cell infiltration, elevated IgE and increased Th2 subset without atopy strongly support a role of Th2‐mediated immunity in DEB‐Pr, and further argue for new targeted therapeutic options such as dupilumab. Abstract : Linked Commentary Z. Ruszczak and S. Abdelhadi. J Eur Acad Dermatol Venereol 2022; 36 : 13–16. https://doi.org/10.1111/jdv.17821 .